1996
DOI: 10.1007/bf00196880
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of rice phytochrome A in tobacco seedlings modifies responsiveness but not competence to phytochrome

Abstract: Abstract.To analyse the control of rice phytochrome A (phyA) overexpression (wild type or variously mutated) on gene regulation, transgenic tobacco lines overexpressing various rice phyA constructs were crossed with transgenic tobacco lines containing mustard Lhcbl or Chsl promoters fused to the uidA reporter gene (13-glucuronidase). It was demonstrated that the temporal pattern of competence to respond to phytochrome was not altered by rice phyA overexpression. Also, overexpression of rice phyA did not change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Hypocotyl elongation and reporter gene expression demonstrated that RW and S/A overexpression leads to enhancement, whereas NTD overexpression causes a suppression of phyA responses (Emmler et al. 1995(Emmler et al. , 1996Stockhaus et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypocotyl elongation and reporter gene expression demonstrated that RW and S/A overexpression leads to enhancement, whereas NTD overexpression causes a suppression of phyA responses (Emmler et al. 1995(Emmler et al. , 1996Stockhaus et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Crossing experiments were performed with plants of the tobacco cultivar SRl bearing promoter GUS reporter genes. These crossings were initiated by a different study where the influence of rice PHYA overexpression on reporter gene expression had been analyzed (Emmler et al, 1996). For the production of seedlings with fused cotyledons, F1 plants from crossings between SR1 pollen acceptors and rice PHYA overexpressor pollen donors were grown to maturity.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous tobacco phyA appears to play little if any role in hook opening and therefore in this instance, although heterologous phyA is able to function in hook opening, it is unlikely to reflect the activity of endogenous protein . Transgenically produced rice phyA does, however, induce the same temporal and spatial pattern of expression from Lhcbl and Chsl promoters as does endogenous phyA (Emmler et al 1996). Therefore, the activity of rice phyA in hook opening may reflect a true but relatively small activity of endogenous phyA, or reflect a fundamental difference between monocot and dicot phytochromes in regulating hook opening.…”
Section: Phenotypes Associated With the Expression Of Phytochrome Tramentioning
confidence: 99%